Highly Pathogenic Avian Influenza Virus A/H5N1 Infection in Vaccinated Meat Duck Flocks in the Mekong Delta of Vietnam. Issue 2 (8th January 2016) - Cuong, N. V.; Truc, V. N. T.; Nhung, N. T.; Thanh, T. T.; Chieu, T. T. B.; Hieu, T. Q.; Men, N. T.; Mai, H. H.; Chi, H. T.; Boni, M. F.; van Doorn, H. R.; Thwaites, G. E.; et al.
Summary: We investigated episodes of suspected highly pathogenic avian influenza (HPAI)‐like illness among 12 meat duck flocks in two districts in Tien Giang province (Mekong Delta, Vietnam) in November 2013. In total, duck samples from 8 of 12 farms tested positive for HPAI virus subtype A/haemagglutinin 5 and neuraminidase 1 (H5N1) by real‐time RT‐PCR. Sequencing results confirmed clade of 2.3.2.1.c as the cause of the outbreaks. Most (7/8) laboratory‐confirmed positive flocks had been vaccinated with inactivated HPAI H5N1 clade 2.3.4 vaccines <6 days prior to onset of clinical signs. A review of vaccination data in relation to estimated production in the area suggested that vaccination efforts were biased towards larger flocks and that vaccination coverage was low [21.2% ducks vaccinated with two shots (range by district 7.4–34.9%)]. The low‐coverage data, the experimental evidence of lack of cross‐protection conferred by the currently used vaccines based on clade 2.3.4 together with the short lifespan of meat duck flocks (60–70 days), suggest that vaccination is not likely to be effective as a tool for control of H5N1 infection in meat duck flocks in the area.